Abdominal obesity as a predictor for response to anti-vascular endothelial growth factor therapy in patients with diabetic macular edema - Tamer E. Wasfy; Shaimaa S. Soliman; Nehad Hawash; Elham A. Gad (Journal of the Egyptian Ophthalmological Society)
Background and aim Diabetic macular edema (DME) is a major cause of visual disturbance among diabetic patients. Anti-vascular endothelial growth factor (anti-VEGF) therapy has been widely used to treat DME. Obesity is associated with higher levels of circulating VEGF, which may worsen diabetic retinopathy and hinder the response to anti-VEGF therapy. This study aimed to assess the effect of abdominal obesity on response to anti-VEGF in patients with DME. Patients and methods The prospective study included 301 eyes of 199 diabetic patients with centrally involved DME. The central macular thickness before and after three consecutive intravitreal injections of anti-VEGF were measured by optical coherence tomography. The patient was considered as having a “poor response” if the central macular thickness has reduced by less than 20% of the pre-injection thickness. The BMI, waist–hip ratio (WHR), and other risk factors were tested for their association with “poor response.” Results The mean age of the included patients was 56.34±9.97 years, and 103 (51.8%) were females. The mean±SD WHR among males was 0.94±0.12, and among females was 0.86±0.07, ranging from 0.68 to 1.16. “Poor response” to therapy was noted in 68 (34.2%) patients. Univariate regression showed that BMI, WHR, fasting blood sugar, and glycosylated hemoglobin were significantly associated with “poor response,” while multivariate regression analysis showed that only glycosylated hemoglobin was significantly associated with “poor response.” Conclusion Abdominal obesity can significantly contribute to “poor response” to anti-VEGF therapy among diabetic patients with DME.